Increased Incidence of Small Intestinal Bacterial Overgrowth During Proton Pump Inhibitor Therapy - Lombardo, Lucio; Foti, Monica; Ruggia, Olga; Chiecchio, Andrea (Clinical gastroenterology and hepatology, 2010)
Proton pump inhibitors (PPIs) can cause diarrhea, enteric infections, and alter the gastrointestinal bacterial population by suppressing the gastric acid barrier. Among patients that received long term PPI treatment, we evaluated the incidence of small intestinal bacterial overgrowth (SIBO; assessed by glucose hydrogen breath test [GHBT]), the risk factors for development of PPI-related SIBO and its clinical manifestations, and the eradication rate of SIBO after treatment with rifaximin. GHBTs were given to 450 consecutive patients (200 with gastroesophageal reflux disease who received PPIs for a median of 36 months; 200 with irritable bowel syndrome [IBS], in absence of PPI treatment for at least 3 years; and 50 healthy control subjects that had not received PPI for at least 10 years). Each subject was given a symptoms questionnaire. SIBO was detected in 50% of patients using PPIs, 24.5% of patients with IBS, and 6% of healthy control subjects; there was a statistically significant difference between patients using PPIs and those with IBS or healthy control subjects ( P < .001). The prevalence of SIBO increased after 1 year of treatment with PPI. The eradication rate of SIBO was 87% in the PPI group and 91% in the IBS group. SIBO, assessed by GHBT, occurs significantly more frequently among long term PPI users than patients with IBS or control subjects. High dose therapy with rifaximin eradicated 87%–91% of cases of SIBO in patients who continued PPI therapy.